2022
DOI: 10.1111/codi.16120
|View full text |Cite|
|
Sign up to set email alerts
|

The use of the faecal immunochemical test during the COVID‐19 pandemic to triage urgent colorectal cancer referrals

Abstract: Aim During the first wave of the COVID‐19 pandemic in 2020, elective gastrointestinal endoscopy services were abbreviated for fear of viral transmission. However, urgent suspected colorectal cancer (CRC) referrals continued. Serendipitously, a national study suggested that a new faecal immunochemical test (FIT) might be helpful in triaging patients with colorectal alarm symptoms. Methods This was a single centre observational study of patients referred using NG12 criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…FIT has rapidly taken off for symptomatic patients and the application is not solely for lowrisk patients as a rule in investigation as per the NICE guidance from 2017 15 . The results of the NICE FIT study demonstrated the high sensitivity of FIT for high-risk patients in primary care as a rule out investigation 16 and FIT has been shown to be safe and effective for TWW patients in the coronavirus pandemic to better allocate diminished endoscopy capacity 17,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FIT has rapidly taken off for symptomatic patients and the application is not solely for lowrisk patients as a rule in investigation as per the NICE guidance from 2017 15 . The results of the NICE FIT study demonstrated the high sensitivity of FIT for high-risk patients in primary care as a rule out investigation 16 and FIT has been shown to be safe and effective for TWW patients in the coronavirus pandemic to better allocate diminished endoscopy capacity 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…16 The results of the NICE FIT study demonstrated the high sensitivity of FIT for high-risk patients in primary care as a rule out investigation, 17 and FIT has been shown to be safe and effective for TWW patients in the coronavirus pandemic to better allocate diminished endoscopy capacity. 18,19 Therefore, we suggest that FIT via DRE could also be applied in primary care as a rule out investigation for potential TWW patients. Furthermore, there is interest growing for repeat FIT to further improve sensitivity [20][21][22] in this situation, DRE sampling may also be the method of choice to obtain the additional test.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies do show that FIT has the potential to be used more widely 9 10 17. Furthermore, recent evidence of the expanded use of FIT in England during the COVID-19 pandemic shows a range of positive outcomes, including reduction in mortality,18 significant reduction in the use of endoscopy without compromising CRC detection rates35 and successful prioritisation of patients with a higher risk of cancer when endoscopy services were severely restricted 36. GPs also had positive views on the use of FIT during the COVID-19 pandemic 37.…”
Section: Discussionmentioning
confidence: 99%